2021
DOI: 10.1158/1538-7445.am2021-lb031
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB031: Plasma based metabolic profiling in metastatic gastrointestinal stromal tumors (GIST)

Abstract: Background: Discovery of oncogenic mutations as targets for cancer therapy revolutionized treatment of GIST and other cancers. However, nearly all patients ultimately progress, which emphasizes the need for development of new tools to assess cancer prognosis and factors associated with benefit of cancer therapies. Altered metabolism is a hallmark of cancer, enabling tumors to proliferate, survive and metastasize. By measuring the complete set of metabolites in an individual (metabolome) it is possible to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed, altered metabolite levels have been observed in many diseases, including diabetes [39], neurodegeneration [40], cancer [4], cardiovascular disease [6], and even aging [3]. Furthermore, in a series of separate studies, we have identified metabolite biomarkers of response (BoRs) that correlate with drug responsiveness for metastatic breast cancer patients treated with CDK4/6 inhibitors as well as the anti-HER2 therapy trastuzumab; and for gastrointestinal stromal tumor (GIST) patients treated with tyrosine kinase inhibitors [41][42][43]. While additional validation studies are required, these preliminary results suggest the exciting possibility that metabolite-based biomarkers have for designing optimal treatment strategies for individual patients, which is a major goal of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, altered metabolite levels have been observed in many diseases, including diabetes [39], neurodegeneration [40], cancer [4], cardiovascular disease [6], and even aging [3]. Furthermore, in a series of separate studies, we have identified metabolite biomarkers of response (BoRs) that correlate with drug responsiveness for metastatic breast cancer patients treated with CDK4/6 inhibitors as well as the anti-HER2 therapy trastuzumab; and for gastrointestinal stromal tumor (GIST) patients treated with tyrosine kinase inhibitors [41][42][43]. While additional validation studies are required, these preliminary results suggest the exciting possibility that metabolite-based biomarkers have for designing optimal treatment strategies for individual patients, which is a major goal of precision medicine.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that using a global, unbiased, multi-dimensional 1 H- 13 C heteronuclear single quantum coherence spectroscopy (HSQC) NMR spectroscopy metabolomics platform coupled with machine learning (ML) techniques, we are able to uncover metabolite-based biomarkers that correlate with disease status and response to therapy [32][33][34]. Further, as metabolomics studies are widely acknowledged to suffer from reproducibility challenges [35][36][37][38], we documented the reproducibility of our platform and how to translate our results for vitro diagnostic development [25,32,33]. In this study, we used our NMR and ML platform to measure plasma metabolites from approximately age/sex-matched PD patients with G2019S LRRK2 mutations and non-PD controls wildtype for LRRK2.…”
Section: Introductionmentioning
confidence: 99%